Trade, energy and growth in G7 countries - Katircio?lu, Salih; Ca?lar, Dilber; Beton Kalmaz, Demet (National Academy of Management eco@nam.kiev.ua Vul. Panasa Myrnogo, 26 Kyiv 01011, 2013)
The main aim of this paper is to investigate the relationship between energy consumption and trade by using econometric analysis for G7 countries covering the period 1960-2010, as those countries are very important actors of the global economy since they all together represent around 90% of global GDP and 80% of global trade. Time series analysis is used to examine the relations between the variables. The present study investigates that real income and international trade are important determinants of energy consumption in G7 countries. The evidence found in this paper could be used to shape the energy policies in G7 countries. © Salih Katircioglu, Dilber Caglar, Demet Beton Kalmaz, 2013.
Keywords: Causality; Economic growth; Energy consumption; G7; Trade